Corporate social responsibility and firm financial performance: the mediating role of productivity - Iftekhar Hasan; Nada Kobeissi; Liuling Liu; Haizhi Wang (Bank of Finland, 2016)
This study treats firm productivity as an accumulation of productive intangibles and posits that stakeholder engagement associated with better corporate social performance helps develop such intangibles. We hypothesize that because shareholders factor improved productive efficiency into stock price, productivity mediates the relationship between corporate social and financial performance. Furthermore, we argue that key stakeholders' social considerations are more valuable for firms with higher levels of discretionary cash and income stream uncertainty. Therefore, we hypothesize that those two contingencies moderate the mediated process of corporate social performance with financial performance. Our analysis, based on a comprehensive longitudinal dataset of U.S. manufacturing firms from 1992 to 2009, lends strong support for these hypotheses. In short, this paper uncovers a productivity-based, context-dependent mechanism underlying the relationship between corporate social performance and financial performance.
URN:NBN:fi:bof-201604201103
Keywords: 330